Trends of Ulnar Collateral Ligament Reconstruction in the United States from 2003 to 2014: Analysis of 3,133 Patients - Olumuyiwa A. Idowu, M.D; Haroutioun H. Boyajian, M.D; Kevin Lindsay-Rivera, M.D; Cody S. Lee, M.D; Michael J. Lee, M.D; Lewis L. Shi, M.D; Aravind Athiviraham, M.D (Elsevier, 2020)
Purpose: The purpose of this study is to investigate the trends concerning ulnar collateral ligament (UCL) reconstruction (UCLR) for athletic injuries within the United States over the years 2003 to 2014. Methods: A retrospective review of the Truven Health Marketscan® Commercial Database was conducted for patients undergoing UCLR. Data was reviewed for patients treated between 2003 and 2014, and the cohort of patients undergoing UCLR was queried using Common Procedural Terminology code 24346. Patients ages 11 to 40 years were included and divided into 6 different age groups, with the rate of UCLR calculated for each group. Results: The overall rate of UCLR increased from 4.4 per million in 2003 to 11.9 per million in 2014 (p < .01). Throughout the same time period, the rate per million increased from 3.3 to 22.1 in 11- to 15-year-olds (p < .01), from 105.4 to 293.2 in 16- to 20-year-olds (p < .01), from 23.1 to 67.0 in 21- to 25-year-olds (p < .01), and from 2.1 to 5.7 in 31- to 35-year-olds (p < .01). There was no significant increase in the rate of UCLR in the age groups of 26 to 30 and 36 to 40 years. Conclusion: UCLR was mostly performed in patients aged 11 to 25 years (96.6%), and specifically most common in those patients aged 16 to 20 years (67.4%). The rate of UCLR procedures increased over time for younger age groups significantly more than for their older counterparts. Clinical Relevance: UCLR rates are increasing in young patients despite efforts addressing injury risk reduction strategies and education for coaches, players, and parents regarding risk factors for UCL injury.